Correction to: Spectrum of movement disorders and neurotransmitter abnormalities in paediatric POLG disease. Issue 6 (19th November 2018) - Papandreou, A.; Rahman, S.; Fratter, C.; Ng, J.; Meyer, E.; Carr, L. J.; Champion, M.; Clarke, A.; Gissen, P.; Hemingway, C.; Hussain, N.; Jayawant, S.; et al.
Abstract : Due to a typesetting error the wrong Table 2 was used. The correct Table 2 is shown here: